Cytotoxic and mutagenic properties of O4-alkylthymidine lesions in Escherichia coli cells. Issue 22 (22nd September 2015) - Wang, Pengcheng; Amato, Nicholas J.; Zhai, Qianqian; Wang, Yinsheng
Abstract: Due to the abundant presence of alkylating agents in living cells and the environment, DNA alkylation is generally unavoidable. Among the alkylated DNA lesions, O 4 -alkylthymidine ( O 4 -alkyldT) are known to be highly mutagenic and persistent in mammalian tissues. Not much is known about how the structures of the alkyl group affect the repair and replicative bypass of the O 4 -alkyldT lesions, or how the latter process is modulated by translesion synthesis polymerases. Herein, we synthesized oligodeoxyribonucleotides harboring eight site-specifically inserted O 4 -alkyldT lesions and examined their impact on DNA replication in Escherichia coli cells. We showed that the replication past all the O 4 -alkyldT lesions except ( S )- and ( R )- s BudT was highly efficient, and these lesions directed very high frequencies of dGMP misincorporation in E. coli cells. While SOS-induced DNA polymerases play redundant roles in bypassing most of the O 4 -alkyldT lesions, the bypass of ( S )- and ( R )- s BudT necessitated Pol V. Moreover, Ada was not involved in the repair of any O 4 -alkyldT lesions, Ogt was able to repair O 4 -MedT and, to a lesser extent, O 4 -EtdT and O 4 - n PrdT, but not other O 4 -alkyldT lesions. Together, our study provided important new knowledge about the repair of the O 4 -alkyldT lesions and their recognition by the E. coli replication machinery.